Sources of Political and Social Unrest in the Peloponnese on the Eve of the Revolution - Kostantaras, Dean (Historein, 2022)
This article explores questions surrounding the motivations of the diverse group of actors who took part in the Greek Revolution. Attention is directed especially towards conditions in the Peloponnese and the actions of local political and military elites. The insights gained from this analysis are further used to consider the extent to which the revolution may be compared, from a standpoint of precipitating causes, social forces and international contingencies, with the other great upheavals associated with the Age of Revolution.